The Puncoviscana Formation and related units in the Neoproterozoic - Early Cambrian transition of Northwest Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Neoproterozoic/Early Cambrian rocks are represented in northwest Argentina by a thick and heterogeneous succession of highly deformed and slightly metamorphosed sedimentary rocks. The denomination of Puncoviscana Formation (s.l.) unifies a series of rock units, represented by scarce fossiliferous slightly metamorphosed slates, schists, carbonates, conglomerates and sandstones cropping out mostly in the Cordillera Oriental of northwest Argentina (Turner, 1960; Turner and Mon, 1979; Aceñolaza et al., 1999) (Fig.1-3, 5). Originally described as the "basal Precambrian shield" of the region, it was reconsidered during the 70's by means of trace fossil associations denoting a Neoproterozoic - Early Cambrian age (Fig. 5). Integration of several lines of research as geochemistry, ichnology and stratigraphy suggest that sedimentation in the Puncoviscana Basin spanned from Neoproterozoic to the Early Cambrian (Fig. 3). The recent usage of the Siberian stages to date some strata of the Puncoviscana Formation has provoqued confusions in the literature, being highly recommended its abandonment. Siberian stages are defined by a precise set of fossils that is lacking in the strata of Northwest Argentina. Petrological and geochemical analysis corroborates a mainly authochthonous Gondwanan continental block origin (peripheral basin), with sedimentary and low grade metamorphic series developed in shallow tectonic stages of a multi-phase orogen. On the basis of general and detailed sedimentological studies, a varied spectrum of environmental settings have been recognized for the Puncoviscana basin since the 60's. Today a complex paleoenvironmental framework is understood, including shallow water wave-influenced strata, submarine fan sedimentation, hemipelagic clays and relatively deep ocean flysch-like shales and sandstones (Fig. 4). Although recent papers deny the presence of body fossils in the unit, the Puncoviscana Formation has provided two remarkable soft body fossils: Selkirkia sp. and Beltanelloides from outcrops of Jujuy and Tucumán provinces (Fig. 8). The ichnological research during the last 30 years contributed with a fairly acceptable knowledge of the paleontological content of the Puncoviscana Formation. Even though this is not a taxonomical contribution, the most obvious equivalences and synonymies are given. An updated review of the trace fossils in the Puncoviscana Formation provides the following list: Archaeonassa fossulata, Asaphoidichnus isp., Cochlichnus anguineus, Didymaulichnus lyelli, Dimorphichnus obliquus, Diplichnites isp., Glockerichnus isp., Helminthoraphe isp., Helminthopsis abeli, Helminthopsis tenuis; Helminthoidichnites tenuis, Monomorphichnus lineatus, Monomorphichnus isp., cf. Multipodichnus, Nereites saltensis (non Psamichnites saltesis, Seilacher et al., 2005), Neonereites uniserialis, N. biserialis, Oldhamia alata, O. antiqua, O. curvata, O. flabellata, O. geniculata, O. radiata, Palaeophycus tubularis, Paleophycus isp. Protichnites isp., Protovirgularia isp., Tasmanadia cachii, Treptichnus isp. Treptichnus cf. aequalternus and T. pollardi (Aceñolaza et al., 1999; Aceñolaza and Alonso, 2001; Aceñolaza, 2004) (Figs. 6-8). The geographical distribution of trace fossil assemblages display a remarkable alignment as belts, with a shallower eastwards Nereites association, and a deeper westwards Oldhamia associacion, that do not represent archetypal ichnofacies (Fig. 4) These are related to the morphology of the basin, a chronological record of the ichnofaunas, and may also represent different temporal levels on the evolution of the Puncoviscana Sea. Within the Oldhamia association most trace fossils are small sized, developed parallel to bedding planes, and bioturbation is essentially restricted to the first millimeters of strata. Deeper burrowers are recognized in the base of sandstone layers of the sequences. This spatial restriction of bioturbation with the frequent presence of wrinkle marks denotes a microbial mat related lifestyles of the fauna as it happens in other Neoproterozoic/Early Cambrian basins (Fig. 8). Within the Nereites association, a more diverse trace fossil set is recognized, with large and mid size grazing and crawling traces developed in sand-mud interfaces. Arthropod traces are common in this association. Integration of sedimentary and paleontological evidence provides remarkable elements to better understand the ecology of Late Proterozoic/Early Paleozoic biota. This contribution gives an updated analysis of the Puncoviscana Formation and related units of the region, offering new lines of evidence for the most recent ideas regarding the Neoproterozoic/Early Cambrian of NW Argentina.
Keywords: Neoproterozoic/Early Cambrian; Puncoviscana Formation; Biostratigraphy; Northwest Argentina